ASPEK PERBUATAN MELAWAN HUKUM MENDIAMI RUMAH DINAS NEGARA BERDASARKAN PP RI NO. 40 TAHUN 1994 TENTANG RUMAH NEGARA - Fitriani Fitriani (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
AbstractCivil Servant, is a profession and a job. Civil servants as well as other professions such as lawyers, public accountants, notaries, employers, consultants, artists, journalists, farmers, factory workers and so forth. Civil servants are not only elements of the state apparatus but also state servants and public servants who always live in the community and work for the benefit of society, therefore in the implementation of the guidance of civil servants not only seen and treated as the State Apparatus, but also viewed and treated as a citizen.The fulfillment of the right to house to the people themselves is mandated to the State as stated in the International Convention on Economic, Social and Cultural Rights, which has been ratified by Law of the Republic of Indonesia Number 11 Year 2005 on the Ratification of International Convenant On Economic, Socialand Cultural Ringhts The International Covenant on Economic, Social and Cultural Rights) in which one of its clauses Section recognizes the right to everyone in respect of housingThe government's efforts to provide assistance solutions for the fulfillment of housing for civil servants (PNS) / state civil servants (ASN) who are still active and retired serve provide assistance solutions made with the procurement of state official houses built for its employees, the government also builds housing to be owned by its inhabitants by repaying through the State Savings Bank (BTN)